(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1864)
This article describes the architecture of some Inca buildings in Peru. The author discusses the Coricancha temple at Cusco, the ruins at Pachacámac, and other stone constructions along the shore of Lake Titicaca. He explains his understanding of the religious significance of these sites to the Inca and other Native Peruvian groups, as well as some of the pre-colonial history of the area. There is also some discussion of Peru’s native languages and the author’s observations of generalised physical characteristics that he associates with different native populations. He comments on several Peruvian skulls that he brought to the Society on the day of his talk and quotes examples that refer to the practice of binding a child’s head to alter the shape of the skull.